'Triangulation:' an expression for stimulating metacognitive reflection regarding the use of 'triplet' representations for chemistry learning - Thomas, Gregory P (Chemistry Education Research and Practice, 2017)
Concerns persist regarding high school students' chemistry learning. Learning chemistry is challenging because of chemistry's innate complexity and the need for students to construct associations between different, yet related representations of matter and its changes. Students should be taught to reason about and consider chemical phenomena using 'triplet' representations. A meta-language to discuss chemistry learning with students regarding these representations and their use is therefore necessary. This paper reports on a classroom intervention in which the teacher used the term 'triangulation' as an expression to stimulate metacognitive reflection in students to consider the importance and use of these representations for their learning of chemistry. Students understood and could elaborate the meaning of triangulation. However, their views of the importance and reported use of cognitive processes associated with it varied across individuals. Despite the variation, this study highlights the potential of developing students' metacognition by explicitly engaging them in considering means of representing the chemistry subject material they are being asked to learn, and how they might learn it using strategies and activities that are aligned with the nature of that material.